A REVIEW OF STUDY AND PERFORMANCE OF PARTIAL DISCHARGE FOR DIFFERENT TYPE OF INSULATION MATERIALS - Patareya, Khushboo; Pachori, Arun (International Journal of Engineering Technologies and Management Research, 2018)
The insulation should be high quality for power transmission and high voltage application, in this way we are studying about the various type of insulation material such as epoxy resin, vulcanized fibres and polyethylene which are having different capacitance value, the power transmission equipment’s has less efficiency due to degradation of insulation material. In this paper, we are studying the partial discharge for the different type of insulation materials.